ESTIMATING THE IMPACT OF CARGO PARAMETERS AND EXTERNAL LOAD ON HELICOPTER CONTROLLABILITY - G. N. Babenko (Научный вестник МГТУ ГА, 2018)
Within the problems solution of complex research in helicopter controllability, the reasons of changes  controllability parameters when transporting cargo using external load have previously been identified.The next stage of research is to determine how concrete cargo parameters and external load as a whole, as well as their combination influence helicopter controllability parameters.The article contains research results of the cargo parameters and external load impact on static and dynamic controllability parameters. As a static characteristic of controllability the operation efficiency expressed by the maximal angular acceleration acquired by the helicopter in the case of throttle equal deviations at various flight velocities was considered. Time of the transient process was chosen as a dynamic characteristic with the observable parameter being the movement of the cyclic pitch. For cargo parameters, 16 combinations of ballistic coefficient and cargo mass were considered, while the external load parameter the cable length from 10 to 40 meters was chosen.According to completed simulation experiments, certain dependencies were found between controllability parameters and external cargo parameters and their various combinations. The analysis of the results showed that the dynamic characteristics are more appropriate for estimating the impact of cargo parameters on helicopter flying qualities, since such estimation fully defines the workload on a pilot. The acquired results may be applied to improve Flight Operations Manuals and Aviation Personnel Training Instructions.